The effects of Caesarean section on lipid peroxidation and some antioxidants in the blood of newborn calves - Erisir, Mine; Kandemir, Fatih M.; Yuksel, Murat (Univ Zagreb Vet Faculty, 2013)
The mode of delivery may have a considerable effect on the state and health of the newborn. Therefore, the purpose of this study was to investigate the effect of a Caesarean section on oxidant and antioxidant status in newborn calves. This study included the neonates of 8 normally calved cows and 8 cows who had undergone by Caesarean section. Malondialdehyde concentrations were significantly higher in the calves delivered by caesarean section compared to the calves of normally calved cows, but catalase activity was significantly lower (P<0.01). Glutathione concentrations tended to increase in the calves delivered by Caesarean section compared to the calves of normally calved cows. There were no significant differences in the glutathione peroxidase activity between the groups. Our results suggest that the malondialdehyde concentrations and catalase activities, which show lipid peroxidation and antioxidant status in newborn calves, change due to Caesarean section. In conclusion, newborn calves are exposed to higher oxidative stress in Caesarean section.
U?inci carskog reza na peroksidaciju lipida i neke antioksidanse u krvi netom oteljene teladi
Keywords: Caesarean section; newborn calves; oxidant and antioxidant status